New principles of forming cost on the passenger transportation - Barash, Yu. S.; Pinchuk, O. P. (Science and Transport Progress, 2011)
In the article the new principles of generating the costs of suburban passenger transportation for each specific train, taking into account features of the rolling stock, traffic speed and comfort are developed.